2017
DOI: 10.3390/ijms18112484
|View full text |Cite
|
Sign up to set email alerts
|

Development of An Impedimetric Aptasensor for the Detection of Staphylococcus aureus

Abstract: In combination with electrochemical impedance spectroscopy, aptamer-based biosensors are a powerful tool for fast analytical devices. Herein, we present an impedimetric aptasensor for the detection of the human pathogen Staphylococcus aureus. The used aptamer targets protein A, a surface bound virulence factor of S. aureus. The thiol-modified protein A-binding aptamer was co-immobilized with 6-mercapto-1-hexanol onto gold electrodes by self-assembly. Optimization of the ratio of aptamer to 6-mercapto-1-hexanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Two of the aptamers (PA#2/8 and PA-C8) are very suitable as capture molecules and in particular PA#2/8 as reporter molecule. We have previously shown that PA#2/8 is functional in different assay designs and is able to recognize intact cells of S. aureus [ 32 ]. Our next steps will focus on the integration of the aptamers in detection assays, e.g., sandwich-type assays like ELONA or lateral flow assays (LFA), which are suitable for the practicable pathogen detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the aptamers (PA#2/8 and PA-C8) are very suitable as capture molecules and in particular PA#2/8 as reporter molecule. We have previously shown that PA#2/8 is functional in different assay designs and is able to recognize intact cells of S. aureus [ 32 ]. Our next steps will focus on the integration of the aptamers in detection assays, e.g., sandwich-type assays like ELONA or lateral flow assays (LFA), which are suitable for the practicable pathogen detection.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described the selection of DNA aptamers for the specific binding to Protein A as a cell surface component of Staphylococcus aureus [ 30 ]. We found one promising aptamer that was extensively characterized and evaluated for its ability to recognize and bind to Protein A in a whole cell context of the bacterial pathogen [ 31 , 32 ]. In this work, we applied NGS to the same selected aptamer pool to compare the outcome with that of Sanger sequencing and perhaps to expand our portfolio of Protein A-binding aptamers.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of impedimetric biosensors for whole bacteria detection have been described in recent years ( Table 1 ). The most common bioreceptors employed in this case are enzymes coated on nanoparticles [ 45 ], antibodies [ 14 , 57 , 58 , 59 , 60 ], aptamers [ 71 ], lectins [ 75 , 76 , 77 ] and phages [ 88 , 89 ]. The use of AMPs represents the main focus of this review and will be covered comprehensively in the following sections.…”
Section: Biosensors For Detecting Bacterial Cellsmentioning
confidence: 99%
“…© 2010 Elsevier B.V. ELECTROCHEMICAL BIOSENSORS: ( A ) Aptamer functionalized impedimetric biosensor. Figure reproduced from [ 71 ]; ( B ) Potentiometric biosensor. Reprinted from [ 70 ], with permission from Elsevier.…”
Section: Figurementioning
confidence: 99%
“…Compared with optical sensors, electrochemical sensors [ 59 , 60 , 61 ] are easy to achieve miniaturization and portability, and can be used for turbid medium detection. Therefore, aptamer-based electrochemical sensors for pathogenic E. coli detection have also attracted much attention [ 62 , 63 , 64 ].…”
Section: Aptamer-based Electrochemical Sensors For Pathogenic mentioning
confidence: 99%